Amphibious seismic refraction and wide-angle data recorded along profile P01 of RV METEOR cruise M69/2 in the Alboran Sea - Grevemeyer, Ingo; Ranero, César R; Díaz, Jordi; Gómez de la Peña, Laura (PANGAEA, 2020)
In August and September of 2006 the seismic WESTMED project was conducted in the Western Mediterranean aboard the German RV "Meteor" during the cruise M69/2. Profile 01 (p01) was recorded sucessfully in the Alboran Sea on 11 onshore stations and 16 offshore stations (ocean-bottom seismometers and hydrophones - OBS/OBH). The offshore stations were distributed every 4.5 km. Shoots were fired offshore along a ~150 km line, using two 32-litres BOLT air-guns array operated at 140 bar, fired every 60 s (~200 m). Total length of the seismic line is 360 km, running from the Gulf of Almeria, Spain southward approaching Morocco. Seismic segy data are reduced at 6 km/s. Please note that records from landstations start at 0 sec while OBS and OBH start at -2 sec.
Keywords: Alboran Sea; Continental crust; crustal strcuture; Miocene island arc